VALIDATION OF SOME RECENT CHILEAN TAXONOMIC NOVELTIES IN ERIOSYCE PHIL. (CACTACEAE) VALIDACION DE ALGUNAS RECIENTES NOVEDADES TAXONOMICAS EN ERIOSYCE PHIL. (CACTACEAE) - John M Watson (Universidad de Concepción, 2006)
A. E. Hoffmann & H. E. Walter (2004) published taxonomic novelties invalidly in the latest edition of their book on Cactaceae in Chile. It also contained an orthographical inaccuracy. All these occur in the genus Eriosyce as revised and expanded by Katterman (1994). They are rectified here with the colaboration of the original authors. Further observations are added about rare and interesting taxa treated in Hoffmann & Walter En la última edición de su libro sobre Cactáceas en Chile, A. E. Hoffmann & H. E. Walter (2004), además de un error ortográfico, publicaron incorrectamente algunas novedades taxonómicas del género Eriosyce, tal como fue revisado y aumentado por Katterman (1994), lo que las hace inválidas. Estos se corrigen aquí con la cooperación de los autores originales. Además se agregan otras observaciones acerca de algunos raros e interesantes taxas tratados por Hoffmann & Walter